An acetate bridged centrosymmetric zinc(II) complex with a tetradentate reduced Schiff base ligand: Synthesis, characterization and ability to sense nitroaromatics by turn off fluorescence response. (1st November 2020) - Mondal, Ipsita; Chatterjee, Sudipta; Chattopadhyay, Shouvik
Graphical abstract: An acetate bridged centrosymmetric zinc(II) complex with a tetradentate reduced Schiff base ligand has been synthesized and characterized. The complex behaves as a sensor for the detection of nitrobenzene in DMF solution via a turn-off fluorescence response. Highlights: Synthesis of an acetate bridged centrosymmetric zinc(II) complex using a reduced Schiff base ligand. Confirmation of the structure by single crystal X-ray diffraction. The complex used as a sensor for the detection of nitroaromatics in DMF via turn-off fluorescence response. Abstract: A unique trinuclear centrosymmetric zinc(II) complex, [Zn3 L2 (CH3 CO2 )2 (DMSO)2 ] has been synthesized and characterized by using a reduced Schiff base ligand H2 L { H2 L  = 1, 3-bis(2-hydroxybenzylamino)2, 2-dimethylpropane}. The complex has been characterized by spectral and elemental analysis. Single crystal X-ray diffraction analysis has confirmed the structure of the complex. The complex has showed strong fluorescence, which may be quenched in presence of different nitroaromatic substances. The complex thus used as a sensor for the detection of nitroaromatics in DMF via turn-off fluorescence response.